Development of a Tantric Meditation Practice: Three Generations of Tibetan Lamas - Cantwell, C (Dharma Drum Buddhist College, 2014)
This paper traces the development of a tantric meditation practice across three generations of Tibetan lamas considered to be linked by reincarnation. The focus is a visualisation practice on the popular tantric deity, Vajrakīlaya (also called, Vajrakumāra). Meditative traditions relating to Vajrakīlaya are ubiquitous in Tibetan sources, including root tantras, transmitted instructions, and fresh revelations. Key passages, such as the verses for the meditative build-up of the maṇḍala, are shared in many sources, but there are also variants characterising different traditions of practice. Exactly how such a tradition of practice is developed over time is explored in the works of the seventeenth century Dudul Dorje (bdud 'dul rdo rje, 1615-1672), the nineteenth century Dudjom Lingpa (bdud 'joms gling pa, 1835-1904), and the twentieth century Dudjom Jigdral Yeshe Dorje (bdud 'joms 'jigs bral ye shes rdo rje, 1904-1987). Dudjom Lingpa, who produced three sets of Vajrakīlaya ritual meditations within his larger revelatory cycles, trained in Dudul Dorje's tradition and became seen as his emanation. Dudjom Lingpa's recognised immediate incarnation, Dudjom Jigdral Yeshe Dorje Rinpoche, was one of the main lineage holders who contributed to new textual compositions for a number of different revelatory traditions, including his work on editing and advancing the revelations of his predecessor, as well as revealing new scriptures himself. Comparisons between the Vajrakīlaya productions of the three lamas show continuities giving the lineage of practice its stamp of identity, while we also witness significant re-working, elaboration, systematisation and codification of the liturgical material and meditative instructions.